(untitled) (Communications in Computational Physics, 2020)
We propose an adaptive threshold dynamics method for wetting problems in three space dimensions. The method is based on solving a linear heat equation and a thresholding step in each iteration. The heat equation is discretized by a cell-centered finite volume method on an adaptively refined mesh. An efficient technique for volume conservation is developed on the nonuniform meshes based on a quick-sorting operation. By this method, we compute some interesting wetting problems on complicated surfaces. Numerical results verify some recent theories for the apparent contact angle on rough and chemically patterned surfaces.